Firm age and crude oil returns: Stock price sensitivity of oil-producing and consuming companies - Hirofumi Nishi (Cogent Economics & Finance, 2020)
This study aims to identify firm characteristics that affect the cross-firm variation in oil-stock interactions. A panel data analysis with a sample of U.S. and Canadian firms reveals that the stock price sensitivity to crude oil price returns is negatively and significantly associated with firm age. Contrary to a common belief, firm size or stock liquidity does not seem to influence heterogeneity in oil-stock relationships. My finding is consistent across oil-producing and consuming companies while the effect of firm age is not observed among financial institutions engaged in commodity trading. An additional test using the panel Granger causality approach shows no lagged effect of oil market movement on the oil and gas extraction firms, suggesting their prompt response to market information.
Keywords: C32; G12; G13; 330; Crude oil price; firm age; panel causality; stock returns